Building and Sustaining a Healthy and Thriving Department - Laura Trujillo-Jenks; Gina Anderson (Academic Chairpersons Conference Proceedings, 2022)
Learning to delegate and build leaders among the faculty and staff, and mentoring and modeling how to manage difficult situations are integral to building and sustaining capacity within a department. Building a department culture that is healthy and thriving, while also creating a climate for faculty and staff to safely develop their own leadership potential are important characteristics of a healthy department. Also, helping faculty and staff learn to mitigate difficult situations is a powerful form of leadership development. Building a culture of success, a climate that nurtures respect, honesty, and loyalty, and engaging in Crucial Conversations© are the foci for this presentation. Activities and recommendations will be shared and discussed.
Keywords: Faculty and staff; healthy organization; difficult situations